2011
DOI: 10.1542/peds.2011-0179
|View full text |Cite
|
Sign up to set email alerts
|

Nonpharmacologic Treatments for Childhood Constipation: Systematic Review

Abstract: OBJECTIVE:To summarize the evidence and assess the reported quality of studies concerning nonpharmacologic treatments for childhood constipation, including fiber, fluid, physical movement, prebiotics, probiotics, behavioral therapy, multidisciplinary treatment, and forms of alternative medicine. METHODS:We systematically searched 3 major electronic databases and reference lists of existing reviews. We included systematic reviews and randomized controlled trials (RCTs) that reported on nonpharmacologic treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 26 publications
0
60
0
5
Order By: Relevance
“…lactis DN-173 010 in this category of patients [103]. No evidence for any effect was found for fluid supplements, prebiotics, probiotics, or behavioral intervention [104]. Until more data are available, probiotics for the treatment of constipation condition should be considered investigational [105].…”
Section: Constipationmentioning
confidence: 99%
“…lactis DN-173 010 in this category of patients [103]. No evidence for any effect was found for fluid supplements, prebiotics, probiotics, or behavioral intervention [104]. Until more data are available, probiotics for the treatment of constipation condition should be considered investigational [105].…”
Section: Constipationmentioning
confidence: 99%
“…Several trials including different types of fibres failed to show any clinically meaningful therapeutic benefit in children 80,81 . Two systematic reviews also illustrate limited clinical value of fibre in the management 82,83 . In addition, increasing dietary fibre intake with extensive behavioural interventions does not reduce the requirement of laxatives 84 .…”
Section: Life Style Modificationsmentioning
confidence: 99%
“…Tabbers MM et al systematically reviewed nonpharmacologic treatments for childhood constipation 6 . They concluded that there is some evidence that fibre supplements are more effective than placebo but no evidence for any effect for fluid supplements, prebiotics, probiotics, or behavioural intervention 6 .…”
Section: Dietary Fibre and Childhood Constipationmentioning
confidence: 99%